Isolation, identification, and antifungal susceptibility of dermatophytes from patients in a tertiary care hospital - Ranganatha, Akash; Rajeswari, Mathigatta Rudrappa (International Journal of Research in Medical Sciences, 2025)
Background: Fungal infections affecting the body’s surface are common in tropical and subtropical climates worldwide. Many antifungal medicines can treat the illness, although the dermatophytes that respond vary by time and site. The study aimed to isolate, identify and analyse the antifungal susceptibility patterns of dermatophytes obtained from patients visiting the dermatology department of a tertiary care hospital. Methods: This 3-month trial included 200 clinically diagnosed individuals with skin and nail dermatophytosis from a tertiary care hospital’s Dermatology outpatient clinic. They consulted the Department of Microbiology to isolate, cultivate and test for fungal sensitivity. Results: Results show that persons aged 21-30 were most profoundly affected. Tinea corporis was the most common clinical symptom at 49.5%, followed by tinea cruris at 24.5%. The most common dermatophytes were Trichophyton species (82.4%). About 67.6% of our isolates had MICs (>1 μg/ml) for fluconazole, regardless of species. The MIC of luliconazole and amorolfine hydrochloride was<0.004 μg/ml for all dermatophytes isolates, while other antifungals had MICs of ≥0.25 μg/ml. The narrowest MIC range was for luliconazole and amorolfine hydrochloride (0.002-0.128 μg/ml), whereas fluconazole and itraconazole had the greatest range (0.125-64 and 0.0321-16) respectively. Conclusions: The study found that luliconazole and amorolfine hydrochloride were the most effective medications against all dermatophytes isolates, followed by itraconazole and fluconazole. Some of our isolates have greater and wider MIC values for itraconazole and fluconazole, which may increase resistance.